Existence and uniqueness of strong solutions to nonlinear nonlocal functional differential equations - Shruti Agarwal; Dhirendra Bahuguna (Electronic Journal of Differential Equations, 2004)
In the present work we consider a nonlinear nonlocal functional differential equations in a real reflexive Banach space. We apply the method of lines to establish the existence and uniqueness of a strong solution. We consider also some applications of the abstract results.